Bilateral Breast Cancer-A Case Report - Ali, Md Yeaqub; Mostafa, SK Golam; Baki, Mollah Obayedullah; Kader, Kazi Manzur; Shamim, Ahsan; Chowdury, Qamruzzaman (Medicine Today, 2010)
We present a case of a 40 year old female who presented with a short history of synchronous, bilateral breast lumps. Core biopsies of both lesions revealed duct cell carcinoma in both breasts. The recognized aggressive course and rapid progression of bilateral synchronous tumors was apparent in our patient. This case illustrates the importance of screening for metastatic disease in patients presenting with bilateral breast lumps. DOI: 10.3329/medtoday.v22i1.5607 Medicine Today Vol.22(1) 2010. 48-49